Identity papers : contested nationhood in twentieth-century France - Ungar, Steven, 1945-; Conley, Tom (University of Minnesota Press, 1996)
What does citizenship mean? The essays in this volume range in subject from fiction and essay to architecture and film. Among the topics discussed are the 1937 Exposition Universelle; films dealing with Vichy France; François Truffaut's Histoire d'Adèle H.; the war of Algerian independence; and nation building under François Mitterrand.